3(x-4)-4(3-x)=x+3-(x-6)

Simple and best practice solution for 3(x-4)-4(3-x)=x+3-(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-4)-4(3-x)=x+3-(x-6) equation:


Simplifying
3(x + -4) + -4(3 + -1x) = x + 3 + -1(x + -6)

Reorder the terms:
3(-4 + x) + -4(3 + -1x) = x + 3 + -1(x + -6)
(-4 * 3 + x * 3) + -4(3 + -1x) = x + 3 + -1(x + -6)
(-12 + 3x) + -4(3 + -1x) = x + 3 + -1(x + -6)
-12 + 3x + (3 * -4 + -1x * -4) = x + 3 + -1(x + -6)
-12 + 3x + (-12 + 4x) = x + 3 + -1(x + -6)

Reorder the terms:
-12 + -12 + 3x + 4x = x + 3 + -1(x + -6)

Combine like terms: -12 + -12 = -24
-24 + 3x + 4x = x + 3 + -1(x + -6)

Combine like terms: 3x + 4x = 7x
-24 + 7x = x + 3 + -1(x + -6)

Reorder the terms:
-24 + 7x = x + 3 + -1(-6 + x)
-24 + 7x = x + 3 + (-6 * -1 + x * -1)
-24 + 7x = x + 3 + (6 + -1x)

Reorder the terms:
-24 + 7x = 3 + 6 + x + -1x

Combine like terms: 3 + 6 = 9
-24 + 7x = 9 + x + -1x

Combine like terms: x + -1x = 0
-24 + 7x = 9 + 0
-24 + 7x = 9

Solving
-24 + 7x = 9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + 7x = 9 + 24

Combine like terms: -24 + 24 = 0
0 + 7x = 9 + 24
7x = 9 + 24

Combine like terms: 9 + 24 = 33
7x = 33

Divide each side by '7'.
x = 4.714285714

Simplifying
x = 4.714285714

See similar equations:

| X-0.2x=32 | | 24n+8=24n-8 | | 5(y-4)=7(2y-1) | | 2x+6+10x-5=25 | | 2x^2+7x+12=o | | 8+4(4x-6)=6-4(2x+1) | | 0.5x+0.15(70)=33.5 | | 14x+15y=100 | | -8x-34+12x=38 | | X/27=18/81 | | -5(3y+2)-10=-6(y+8)+3y | | 4(x+144444)=999999999999 | | (3X-2).5=125 | | 1.60(.2y-y)(.1-y)=y | | 4x+4=-3+2x+21 | | 0.5(x+100)=0.55x-330 | | 2x+1-4(x+1)=6x+2 | | sin(2x)-sin(0.5x)=0 | | 3y-9y=10 | | 5y-3=9+y | | 243/2/3 | | 1+8x^3=0 | | -3x+17=11x+4 | | 3+3m=6 | | 2x+3y+4z=1000 | | 2=x-2m | | xy^2=-10 | | 2/3(y-6) | | 25y^2+13=178 | | 2cos^2+5cosx-3=0 | | 97/2yx2 | | (3ty)(-8t)= |

Equations solver categories